Frequency of Microscopic Colitis among Clinically Suspected Diarrhea Predominant IBS Patients - Podder, Palash Kumar; Masud, Mahadi; Saha, Ujjal Kumar; Ferdoush, Kazi Azajul; Sharifunnesa; Najib, Khandaker Aman Abdullah; Karmaker, Partha Pratim; Islam, M M Shahin Ul; Huq, Mohammad Fazlul; Morshed, Mamun; et al. (Faridpur Medical College Journal, 2026)
Background: Microscopic Colitis (MC) and diarrhea predominant irritable bowel syndrome (IBS-D) has almost same clinical feature. Every day, new cases are diagnosed as IBS-D but how many of them are a case of MC is not usually determined and very few studies are found. This study will help to assess the frequency of MC in clinically suspected IBS-D. Materials & Methods: A cross-sectional observational study was conducted in department of medicine and gastroenterology in Faridpur Medical College Hospital over a period of 6 months from July’15 to December’15. Total 100 clinically suspected IBS-D patients were selected by purposive sampling technique. Then full colonoscopy was done and biopsy was taken from colonic mucosa for histopathology. Results: Out of total 100 patients, 38 had lymphocytic Colitis (LC), 39 had nonspecific microscopic colitis (NSMC), 14 had irritable bowel syndrome non-inflamed (IBSNI) and 9 had others (macroscopically colon had hyperaemia, ulcer). Conclusion: Clinical symptom-based criteria for IBS-D are not specific enough to rule out the diagnosis of MC. Therefore, patients with IBS-D should undergo colonoscopy and biopsies of the colon for histopathology to investigate for possible MC. Faridpur Med. Coll. J. 2026;21(1):17-21